Respuestas

2014-01-03T01:44:01+01:00
2*( x^{2}-2*x*4+ 4^{2})- ( x^{2} +2*3*x+ 3^{2} )= x^{2} +3*x-x-3
 2*x^{2}-2*8*x+ 16*2 -  x^{2} -2*3*x- 3^{2} = x^{2} +3*x-x-3
 x^{2}-16*x+ 32 -6*x- 9 = x^{2} +2*x-3
 -16*x+ 32 -6*x- 9 = 2*x-3
 -24*x+ 23 = -3
 -24*x = -26
 x = -26/-24
 x = 13/12
LAS ALTERNATIVAS SON: 1/4 13/12 1/2 -1 -2
Lapsus. Corregido.
2014-01-03T01:48:01+01:00
2x2  - 16 – x2 + 9 = x2 + 3x – x- 3 X2 – 7 = x2 + 2x – 3 X2 – x2   - 2x= 4 X= -2
LAS ALTERNATIVAS SON: 1/4 13/12 1/2 -1 -2
-2
ME EQUIVOQUE ES 2
oww! :/